Correction of accelerated autoimmune disease by early replacement of the mutated lpr gene with the normal Fas apoptosis gene in the T cells of transgenic MRL-lpr/lpr mice. - Wu, J (1994)
MRL-lpr/lpr mice develop a generalized autoimmune disease which includes increased autoantibody production, glomerulonephritis, and development of lymphadenopathy. The lpr genetic defect has been identified as a mutation in the Fas apoptosis gene that results in low expression of Fas mRNA. To determine the significance of the lpr mutation and T cells in the development of the autoimmune disease, we constructed transgenic MRL-lpr/lpr mice using a full-length murine Fas cDNA under the regulation of the T-cell-specific CD2 promoter and enhancer. Here we show that the early correction of the lpr gene defect in T cells eliminates glomerulonephritis and development of lymphadenopathy and decreases the levels of autoantibodies. In this model, early correction of the lpr defect in T cells is sufficient to eliminate the acceleration of autoimmune disease even in the presence of B cells and other cells that express the mutant lpr gene.